Comparing the costs of radiology and CT-scan services in two hospitals affiliated to Isfahan University of Medical Sciences with approved tariffs and studying resource capacity using Time- Driven Activity Based Costing (TDABC) Method - nasrin Shaarbafchi zade; alireza jabbari; mehri hashemian (Tehran University of Medical Sciences, 2019)
Background: Calculating the cost of services enables the existing resources to be used in the most efficient and effective way possible. Time- Driven Activity Based Costing is a method that, in addition to costing, also calculates the efficiency and unused capacity of resources. The purpose of this study was to use this method to calculate the costs of radiology and CT scans services in two hospitals.   Materials & Methods: The present cross-sectional and retrospective research was done in a descriptive-analytic manner in two hospitals affiliated to Isfahan University of Medical Sciences in 2018. Data were collected in designed Excel forms, and costs of services were calculated using Time- Driven Activity-Based Costing (TDABC) method.    Results: The cost of most radiology services and total CT scan services in the government sector was more than that of the private sector. The unused capacity of resources in the public sector was more than private sector. The time spent for providing the services in the two hospitals was the same except for the technicianchr('39')s career. The average cost of radiology services was 223324 in hospital (A), and 194094 Rials in hospital (B). The average cost of the CT scan services was 600522 in hospital (A), and 485230 Rials in hospital (B).   Conclusion: According to the findings of the study, the need for human resources management to reduce unused capacity and increase efficiency, as well as improving service delivery processes in order to reduce the time required to provide services seems necessary. Replacing low-cost resources is another solution that is effective in reducing costs. The standards of the most efficient centers of health services are often worth the benchmarking.